Interfaith Premarital Education in Cirebon and Its Impacts on Family Resilience: A Comparative Study - Hilmi, Muhammad; Asyrof, Muhammad Najib (Universitas Islam Indonesia, 2025)
This study comparatively examines the design, implementation, and impacts of interfaith marriage guidance in Cirebon Regency, filling the gap related to the different approaches to premarital education in a multireligious environment. This study compares Marriage Guidance (Bimbingan Perkawinan/Bimwim) at KUA Sumber and KUA Kedawung, Marriage Preparation Coaching at St. Joseph Church (Catholic), and Premarital Counseling at Indonesian Christian Church/GKI Pengampon (Protestant). The study aims to: 1) compare premarital counseling methods across institutions; 2) identify the benefits couples experience after following guidance; and 3) explore the bride-to-be's perception of the concept of a harmonious family. This study employs a qualitative- descriptive-comparative approach, utilizing in-depth interviews, observations, and document reviews, with informants selected purposively. The results of the study show: (1) there are differences in design and governance: KUA’s Bimwin is short-intensive with standardized modules, Catholic Marriage Preparation Coaching combines structured courses and canonical investigation, while GKI implements 3–6 months of tiered counseling; (2) the benefits felt by interfaith couples are relatively similar, in the form of improved communication, conflict management, financial literacy, and strengthening spirituality, although the specific nuances vary according to the institution’s traditions; and (3) the perception of a harmonious family converges on three main dimensions: healthy communication, acceptance of the spouse, and long-term commitment, with different accents on each religion. These findings confirm that premarital guidance, although different in terms of curriculum and methods, plays a significant role in equipping couples practically, emotionally, and spiritually to build harmonious families.